Respiratory syncytial virus, human bocavirus and rhinovirus bronchiolitis in infants. Issue 1 (11th October 2009) - Midulla, F; Scagnolari, C; Bonci, E; Pierangeli, A; Antonelli, G; De Angelis, D; Berardi, R; Moretti, C
Abstract : Objective: To investigate the prevalence of 14 viruses in infants with bronchiolitis and to study demographic and clinical differences in those with respiratory syncytial virus (RSV), human bocavirus (hBoV) and rhinovirus (RV) infection. Methods: 182 infants aged <12 months hospitalised for bronchiolitis were enrolled. Infants underwent nasal washing for the detection of RSV, influenza virus A and B, human coronavirus OC43, 229E, NL-63, HUK1, adenovirus, RV, parainfluenza 1–3, human metapneumovirus and hBoV. Demographic, clinical and laboratory data were obtained from parents and from patient medical files. Main outcome measurements were age, breastfeeding history, family smoking habits, family history for asthma and atopy, blood eosinophil count, chest radiological findings, clinical severity score and number of days of hospitalisation. Results: A virus was detected in 57.2% of the 182 infants. The most frequently detected viruses were RSV (41.2%), hBoV (12.2%) and RV (8.8%). Infants with dual infections (RSV and hBoV) had a higher clinical severity score and more days of hospitalisation than infants with RSV, RV and hBoV bronchiolitis (mean±SD: 4.7+2.4 vs 4.3±2.4 vs 3.0±2.0 vs 2.9±1.7, p<0.05; and 6.0±3.2 vs 5.3±2.4 vs 4.0±1.6 vs 3.9±1.1 days; p<0.05). Infants with RV infection had higher blood eosinophil counts than infants with bronchiolitis from RSV and hBoV (307±436 vs 138±168 vs 89±19 n/mm 3 ; p<0.05). Conclusions: Although the major pathogen responsible for bronchiolitis remains RSV, the infection can also be caused by RV and hBoV. Demographic characteristics and clinical severity of the disease may depend on the number of viruses or on the specific virus detected.